Semaglutide combined with empagliflozin vs. monotherapy for non-alcoholic fatty liver disease in type 2 diabetes: Study protocol for a randomized clinical trial. - Yu-Hao Lin; Zhi-Jun Zhang; Jin-Qing Zhong; Zhi-Yi Wang; Yi-Ting Peng; Yan-Mei Lin; Huo-Ping Zhang; Jian-Qing Tian (PLoS ONE)
Background Nonalcoholic fatty liver disease (NAFLD) is strongly associated with type 2 diabetes mellitus (T2DM). Lifestyle intervention remains a preferred treatment modality for NAFLD. The glucagon-like peptide (GLP-1) receptor agonists and sodium-glucose cotransporter-2 (SGLT-2) inhibitors have been developed as new glucose-lowering drugs, which can improve fatty liver via an insulin-independent glucose-lowering effect. However, studies exploring the efficacy of GLP-1 receptor agonists combined with SGLT-2 inhibitors in patients with NAFLD and T2DM are scanty. Thus, the present randomised controlled trial aims at comparing the efficacy and safety of semaglutide plus empagliflozin with each treatment alone in patients with NAFLD and T2DM. Methods This 52-week double-blinded, randomised, parallel-group, active-controlled trial evaluates the effects of semaglutide, empagliflozin and semaglutide + empagliflozin in 105 eligible overweight/obese subjects with NAFLD and T2DM. The primary outcome will be a change from baseline to week 52 in the controlled attenuation parameter, free fatty acid and glucagon. Secondary endpoints include changes in liver stiffness measurement, liver enzymes, blood glucose, lipid levels, renal function, electrolyte balances, minerals and bone metabolism, cytokines, high-sensitivity C-reactive protein, ferritin, anthropometric indicators, nonalcoholic fatty liver fibrosis score, fibrosis 4 score and homeostatic model assessment for insulin resistance. In addition, intention-to-treat, interim analysis and safety analysis will be performed. Discussion This double-blinded, randomised, clinical trial involves a multi-disciplinary approach and aims to explore the synergistic effects of the combination of semaglutide and empagliflozin. The results can provide important insights into mechanisms of GLP-1 receptor agonists and/or SGLT-2 inhibitors in patients with NAFLD and T2DM. Trial registration This study has been registered with Chinese Clinical Trial Registry (ChiCTR2300070674).